2020
DOI: 10.1136/bmjopen-2020-041901
|View full text |Cite
|
Sign up to set email alerts
|

What are the volume and budget needs to provide chemotherapy to all children with acute lymphoblastic leukaemia in Thailand? Development and application of an estimation tool

Abstract: ObjectiveInsufficient access to anticancer medicines may contribute to the wide survival differences of children with cancers across the globe. We developed a tool to estimate the volume of medicines and budget requirements to provide chemotherapy to children with acute lymphoblastic leukaemia (ALL).DesignDevelopment and application of an estimation tool.SettingPaediatric oncology hospital departments in Thailand.Participants318 children aged 0–14 years diagnosed with ALL and 215 children with undiagnosed ALL.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…The QALY of this study is similar to other protocols but its varied in costs relatively [17,18]. Similar studies among other worlds countries showed that in European countries and USA the cost is much higher than the cost of similar protocols in other Asian and American countries [19], but based on the demographic characteristics in table 4-3 the average age of the children is about 9 years and the incidence and prevalence of the disease in hoys is always more than of girls which is similar in other studies [10]. the average length of hospitalization is an important factor influencing the cost of treatment as this study indicates a significant difference in the cost difference between the two protocols.…”
Section: Discussionsupporting
confidence: 80%
“…The QALY of this study is similar to other protocols but its varied in costs relatively [17,18]. Similar studies among other worlds countries showed that in European countries and USA the cost is much higher than the cost of similar protocols in other Asian and American countries [19], but based on the demographic characteristics in table 4-3 the average age of the children is about 9 years and the incidence and prevalence of the disease in hoys is always more than of girls which is similar in other studies [10]. the average length of hospitalization is an important factor influencing the cost of treatment as this study indicates a significant difference in the cost difference between the two protocols.…”
Section: Discussionsupporting
confidence: 80%
“…Five studies were exclusive to long‐term cancer survivors, two of which were 3‐ and 5‐year post cancer diagnosis 25,26,28,30,54 . In the rest of the studies, participants either were still with cancer, 27,29,32,34,35,42,44–47,55 within 1‐year post diagnosis 37,49,50 or up to 3‐year post diagnosis 31,33,53 …”
Section: Resultsmentioning
confidence: 99%
“…More than half of the studies (n = 16, 53%) reported costs for both children and adolescents 0-19 years. Other studies were exclusive to children 0 to 14 years (n = 4, 13%), 39,[47][48][49] AYA aged 15 to 39 years (n = 5, 17%), 25,26,30,33,36 or adolescents 15 to 19 years (n = 1, 3%). 40 Four studies (n = 4, 13%) covered the whole spectrum of children and AYA aged 0-39 years 27,28,31,46 (Table 1, Table S1).…”
Section: Participant Age Groupmentioning
confidence: 99%
See 2 more Smart Citations